1984
DOI: 10.1021/ja00332a049
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin endoperoxides. 14. Solvent-induced fragmentation of prostaglandin endoperoxides. New aldehyde products from PGH2 and a novel intramolecular 1,2-hydride shift during endoperoxide fragmentation in aqueous solution

Abstract: product is not thiocyanate but either the product of its further reaction with BrCN according to eq 1 or a further decomposition product of S(CN)2.BrCN + -SCN -Br + S(CN)2(1)The reactions of ADPaS and ATP0S are not useful for synthesizing adenosine 5'-[180]diphosphates or -triphosphates with chiral Pa or Pd because of the oxygen rearrangements in the polyphosphate systems described herein. These can be prevented by protecting the terminal phosphoryl groups with removable alkyl substituents, as demonstrated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
93
0
2

Year Published

1985
1985
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 1 publication
0
93
0
2
Order By: Relevance
“…4B). Salomon and coworkers (38) have shown that the prostaglandin endoperoxide 10 undergoes a solventinduced fragmentation in phosphate buffer (0.2 M sodium phosphate, pH 7.9) at 37°C to give 9 in 22% yield. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4B). Salomon and coworkers (38) have shown that the prostaglandin endoperoxide 10 undergoes a solventinduced fragmentation in phosphate buffer (0.2 M sodium phosphate, pH 7.9) at 37°C to give 9 in 22% yield. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported that IsoP endoperoxide intermediates also undergo rearrangement to form highly reactive ␥-ketoaldehyde levuglandin-like compounds (4). 2 We propose to term these nonenzymatically generated ␥-ketoaldehydes isoketals (IsoKs) to distinguish them from levuglandins formed by rearrangement of the cyclooxygenase endoperoxide intermediate, PGH 2 (5). These extremely reactive molecules form covalent adducts with lysine residues on proteins at a rate that exceeds that of 4-hydroxy-2-nonenal (4-HNE) by orders of magnitude, which is considered to be one of the most reactive aldehydes generated as a product of lipid peroxidation (6).…”
mentioning
confidence: 99%
“…Inspired by the model studies, we then showed that rearrangement of PGH 2 in neutral aqueous solution not only generates PGD 2 and PGE 2 but also two levulinaldehyde derivatives with prostaglandin side chains, which we named levuglandin (LG) E 2 and LGD 2 ( Fig. 1) [5]. We confirmed the structures of LGE 2 and LGD 2 by total syntheses [6,7].…”
Section: Prostanoid Endoperoxides Rearrange To Give Levulinaldehydesmentioning
confidence: 72%
“…1) is involved since hydrogen bonding by protic solvents accelerates the reaction by two orders of magnitude over the rate in aprotic solvents of similar polarity [4]. Isotopic labeling and kinetics experiments showed that water promotes intramolecular migration of a bridgehead hydride in concert with cleavage of C -C and O -O bonds [5]. These observations led us to predict that as yet unknown products should be readily formed by rearrangements of PGH 2 .…”
Section: Prostanoid Endoperoxides Rearrange To Give Levulinaldehydesmentioning
confidence: 93%